2020
DOI: 10.1016/j.psj.2020.04.021
|View full text |Cite
|
Sign up to set email alerts
|

Functional/physicochemical properties and oxidative stability of ground meat from broilers reared under different photoperiods

Abstract: Long photoperiods are used in the broiler industry to maximize animal performance, though the impact on meat quality remains poorly understood. The current study evaluated the impact of photoperiod on functional/physicochemical properties and oxidative stability of meat through broiler processing. Ross 308 broilers (n = 432) were randomly assigned to 4 photoperiod treatments (hours in L = light, D = dark): 20L:4D, 18L:6D, 16L:8D, or 12L:12D with 6 pens per treatment. At 42 D of age, 2 broilers per pen (n = 12 … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
0
2

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 12 publications
(8 citation statements)
references
References 37 publications
0
6
0
2
Order By: Relevance
“…Goo et al [ 21 ] reported that pH of chicken meat was not affected stocking density (15.2, 20.2, 25.3, or 30.4 birds/m 2 ). Tuell et al [ 22 ] investigated the effect of photoperiod length (L = light, D = Dark, 20 L:4 D, 18 L:6 D, 16 L:8 D, or 12 L:12 D) on chicken meat and reported that photoperiod had no impact on meat pH. In this study, this suggested that the farming system such as that level of stocking density and photoperiod did not affect pH of meat.…”
Section: Resultsmentioning
confidence: 71%
“…Goo et al [ 21 ] reported that pH of chicken meat was not affected stocking density (15.2, 20.2, 25.3, or 30.4 birds/m 2 ). Tuell et al [ 22 ] investigated the effect of photoperiod length (L = light, D = Dark, 20 L:4 D, 18 L:6 D, 16 L:8 D, or 12 L:12 D) on chicken meat and reported that photoperiod had no impact on meat pH. In this study, this suggested that the farming system such as that level of stocking density and photoperiod did not affect pH of meat.…”
Section: Resultsmentioning
confidence: 71%
“…However, there are some controversial reports questioning the long photoperiods application in broiler industry. It was reported [ 6 ] that 12 L:12 D photoperiod improves meat quality attributes in Ross 308 broilers chickens, compared with long photoperiod (20 L: 4 D). Also, near-constant photoperiod (23 L:1 D) increases stress and fear levels in Ross 308 broilers chickens [ 7 ], disrupts circadian clock gene expression and cecal microbiome diversity in Hy-Line Brown Layer chickens [ 8 ].…”
Section: Introductionmentioning
confidence: 99%
“…It is better to use intermittent light during duck feeding or only short light in the early stages to maintain a higher redness value of duck meat ( Starčević et al, 2021 ). Dim light reduces the brightness of broiler meat color ( Fidan et al, 2017 ), whereas long light makes the chicken meat color lighter and increases muscle lipid oxidation and protein denaturation ( Tuell et al, 2020b ). Prolongation of the photoperiod may negatively affect muscle oxidative stability and color by altering muscle metabolites ( Tuell et al, 2020a ).…”
Section: Introductionmentioning
confidence: 99%